2020
DOI: 10.21123/bsj.2020.17.3.0760
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Characterization of a Cyclin Dependent Kinase -A (CDKA) and its Coding Gene in some Oryza Species

Abstract: Rice (Oryza sativa) is a fundamental food for the majority of world population. Cyclin Dependent Kinase -A (CDKA) accelerates transition through different stages of cell cycle and contributes in gametes formation. In the present investigation, a CDKA encoding gene along with the corresponding protein were characterized in O. sativa Indica Group, O. glaberrima,  O. barthii, O. brachyantha, O. glumipatula, O. longistaminata, O. meridionalis, O. nivara, O. punctata and O. rufipogon using in silico analyses. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Regarding morphological changes, the senescence cell has an irregular shape and increased lysosomal content (39)(40)(41). A study carried out in mice revealed that mice exposed to stress can activate pathway of p53/p21 and p16INK4a and p21 that are involved in senescence (42,43). Another study showed that injection of mice with endocrine mediators can activate pathway of p53/ p21that is involved in senescence (44).…”
Section: Cellular Senescence Mediates the Aging Processmentioning
confidence: 99%
“…Regarding morphological changes, the senescence cell has an irregular shape and increased lysosomal content (39)(40)(41). A study carried out in mice revealed that mice exposed to stress can activate pathway of p53/p21 and p16INK4a and p21 that are involved in senescence (42,43). Another study showed that injection of mice with endocrine mediators can activate pathway of p53/ p21that is involved in senescence (44).…”
Section: Cellular Senescence Mediates the Aging Processmentioning
confidence: 99%
“…The in silico analyses were recruited to identify several important genes in Oryza species including genes encoding enzymes controlling shikimate pathway (13), salt stress responsive genes (14), regulatory elements for pathogenesis-related proteins (15), nucleotide binding site-leucine-rich repeats playing an important role in the plant defense (16) and Cyclin dependent kinase B (CDKB) gene (17).…”
Section: Introductionmentioning
confidence: 99%